Factor XI Activation by Meizothrombin: Stimulation by Phospholipid Vesicles Containing both Phosphatidylserine and Phosphatidylethanolamine - Borne, Peter A Kr von dem; Mosnier, Laurent O; Tans, Guido; Meijers, Joost C M; Bouma, Bonno N (Thrombosis and Haemostasis, 1997)
The activation of factor XI by meizothrombin was investigated using recombinant meizothrombin (R155A meizothrombin) that is resistant to autocatalytic removal of fragment 1. Meizothrombin was capable of activating factor XI at an activation rate similar to that of thrombin. Dextran sulphate and heparin, known cofactors of thrombin-mediated factor XI activation, did not stimulate the activation of factor XI by meizothrombin. However, the activation of factor XI by meizothrombin was markedly enhanced by vesicles containing phosphatidylcholine (PC), phosphatidylserine (PS) and phosphatidylethanolamine (PE), whereas PC/PS or PC/PE vesicles only had a minor effect on the activation. Thrombin-mediated factor XI activation was not influenced by phospholipids.The effect of PC/PS/PE and PC/PS vesicles was studied in a factor XI dependent clot lysis assay. In this assay, factor XI inhibits clot lysis by a feedback loop in the intrinsic pathway via thrombin-mediated factor XI activation. Removal of endogenous phospholipids in plasma by centrifugation resulted in an increased clot lysis, which could be restored to the pre-centrifugation level by the addition of PC/PS/PE vesicles, but not by PC/PS vesicles. When clot lysis was initiated by factor IXa in the presence of a factor XIa blocking antibody, there was no difference in inhibitory effect of PC/PS/PE or PC/PS vesicles. These data suggested that the differences in clot lysis inhibition observed between PC/PS/PE and PC/PS vesicles were caused by factor XI activation by meizothrombin. Meizothrombin-mediated factor XI activation may therefore play an important role in the antifibrinolytic feedback loop in the intrinsic pathway.